Legal Protection of Public WiFi Users from Cyber Crime - Amin, Muhammad Yusuf; Isnaeni, Diyan; Sri Utami, Nofi (JURNAL MERCATORIA, 2024)
This research explores the legal protection of public WiFi users from cybercrime, with a focus on public awareness, security standards, and law enforcement. The main findings show that the public's low awareness of public WiFi security risks is caused by a lack of education and information, wrong perceptions of security, and dependence on technology. Additionally, security standards implemented by public WiFi service providers vary and are often inadequate, influenced by a lack of strict regulation, implementation costs, and lack of technical knowledge. Law enforcement against cybercrime has also proven weak, with limited resources, lack of international cooperation, and inadequate regulations as the main causes. This research recommends increasing public education, strengthening security regulations, increasing law enforcement capacity, and better international cooperation. The implementation of these steps is expected to create a safer digital environment and increase legal protection for public WiFi users from the threat of cybercrime.